2013
DOI: 10.7205/milmed-d-12-00384
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on the Unique Challenges of Female Soldiers' Reproductive Issues in a War-Ready Culture

Abstract: In 1951, a U.S. Presidential Executive Order outlined regulations governing the involuntary separation of women from military service in the event of pregnancy, parenting, or giving live birth while on commissioned service. Subsequent public law and court decisions have changed the rules on female soldier pregnancy and parenting. Initially capped at 2%, maximum allowable percentage of the military, female soldiers now comprise over 14% of the U.S. active duty military, numbering over 200,000. The issues of sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They act as nurses, signalman, helmsman and so on. In comparison, previous data reported that women accounted for 10.5% of the service personnel on aircraft carriers of US Navy by the end of 1995 3…”
Section: Introductionmentioning
confidence: 61%
“…They act as nurses, signalman, helmsman and so on. In comparison, previous data reported that women accounted for 10.5% of the service personnel on aircraft carriers of US Navy by the end of 1995 3…”
Section: Introductionmentioning
confidence: 61%
“…A female soldier's reproductive ability and family planning affects soldier readiness and deployment planning (Fitzgerald et al, 2013). Women who have served in recent conflicts are primarily of reproductive age; thus, reproductive health disorders, such as sexually transmitted infections, menstrual disorders, and infertility, and their association with combat-related mental health disorders, are particularly important areas to investigate.…”
Section: Articlementioning
confidence: 99%
“…Obviously, this was also an attempt to avoid further outcomes stemming from any unintended pregnancies and/or testing military abortion restrictions (Holt, Grindlay, Taskier, & Grossman, ; Manski, Grindlay, Burns, Holt, & Grossman, ). For 2 months in 2009, pregnancy was one reason leading to an initiation of court‐martial proceedings (Fitzgerald et al., ). While this order was quickly rescinded, it still provided an informal threat and sometimes produced outcomes of self‐ or peer‐inflicted abortions, especially if the pregnancy followed MST and/or the danger of an out‐of‐combat‐zone medical evacuation (ACOG, ; Cohen et al., ; Grindlay et al., ; Holt et al., ; Jacobson & Jensen, ; Lindberg, ; Polomano & Stringer, ).…”
Section: Difficultiesmentioning
confidence: 99%
“…During the GWOT, between 39% and 77% of women used contraceptives, yet the scientific data on their use remain limited. These medications, including emergency contraceptives, were supposed to be available, although there were multiple problems primarily with privacy and accessibility difficulties (Fitzgerald et al, 2013;Holt et al, 2011;Manski, Grindlay, Burns, Holt, Grossman, 2014).…”
Section: Reproductive/gynecological/urinary Issuesmentioning
confidence: 99%